WISDOM DICTIONARY IN MODERN EDUCATION - Xolnazarova Dinara; Poʻlatova Sevinch; Tolibjonova Munisa (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation This article discusses the role of a “Wisdom Dictionary” in modern education and its impact on students’ intellectual and personal development. A wisdom dictionary is a collection of meaningful words, expressions, and life lessons that help learners expand their vocabulary and understand deeper meanings of language. The study shows how using such a dictionary can improve critical thinking, moral awareness, and communication skills. It also highlights how students can connect language learning with real-life experiences.